2018
DOI: 10.1186/s12861-018-0176-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex on response of the bovine preimplantation embryo to insulin-like growth factor 1, activin A, and WNT7A

Abstract: BackgroundAlterations in maternal environment can sometimes affect embryonic development in a sexually-dimorphic manner. The objective was to determine whether preimplantation bovine embryos respond to three maternally-derived cell signaling molecules in a sex-dependent manner.ResultsActions of three embryokines known to increase competence of bovine embryos to develop to the blastocyst stage, insulin-like growth factor 1 (IGF1), activin A, and WNT member 7A (WNT7A), were evaluated for actions on embryos produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Furthermore, the Wnt signaling pathway plays an important role in embryogenesis and cancer development by regulating the expression of genes involved in cell proliferation, differentiation and survival (22). Wnt7a, one of Wnt ligands, activates the canonical Wnt/β-catenin signaling pathway to promote cell proliferation (23). Previous studies have revealed that Wnt7a expression is dysregulated in several tumors, including gastric, lung, liver, pancreatic, colorectal, cervical and breast cancers (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Wnt signaling pathway plays an important role in embryogenesis and cancer development by regulating the expression of genes involved in cell proliferation, differentiation and survival (22). Wnt7a, one of Wnt ligands, activates the canonical Wnt/β-catenin signaling pathway to promote cell proliferation (23). Previous studies have revealed that Wnt7a expression is dysregulated in several tumors, including gastric, lung, liver, pancreatic, colorectal, cervical and breast cancers (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is regulation of the epigenome of the developing trophoblast. The capability of DKK1 to introduce epigenetic modifications has been observed in hepatic stellate cells where DKK1attenuates MeCP2 enrichment in the Pparγ promoter and H3K27me2 enrichment in exon 5 of the same gene 55 . A recent report focused on regulation of the transiently imprinted Zdbf2 locus in the mouse has illustrated how regulation of DNA methylation in the preimplantation period can have consequences for phenotype as late as the adult period 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-like growth factor 1 levels are higher in younger growing animals and possibly involved in metabolic programming [41][42][43]. The addition of physiological concentrations of IGF1 (10-100 ng/mL) improved the developmental competence of bovine early embryos in vitro [44][45][46]. In mice, a study using a high IGF1 concentration, i.e.…”
Section: Sncrnas As Epigenetic Inheritance Factorsmentioning
confidence: 99%